Optical Fiber‐Based Wearable Sensors for Remote Health Monitoring [Invited] - Guiwei Zhang; Ragini Singh; Bingyuan Zhang; Guoru Li; Santosh Kumar (Advanced Sensor Research)
Abstract The wearable optical fiber sensors have demonstrated significant promise in the realm of health monitoring in recent times. These sensors utilize the flexibility and exceptional sensitivity of optical fibers to precisely measure many physiological aspects of the human body, including heart rate, breathing rate, mobility status, and body temperature. Optical fiber sensors usually have good biocompatibility and anti‐interference capabilities, can be integrated into flexible materials, and are suitable for long‐term wear. It can be integrated into clothing, patches, or accessories to provide continuous, real‐time health data monitoring, providing important support for personalized medicine and remote health management. This paper primarily presents the fundamental operating concept of wearable optical fiber sensors and their use in monitoring physiological signals across multiple domains. In conclusion, this paper provides a summary of the limitations and future prospects of wearable fiber sensors using optical fiber technology.